The Romani Gypsies - Matras, Yaron, 1963- 1963- (The Belknap Press of Harvard University Press, 2015)
Who are the Romani people? -- Romani society -- Customs and traditions -- The Romani language -- The Roms among the nations -- Between romanticism and racism -- A modern Romani identity -- Appendix: The mosaic of Romani groups